Energy consumption, CO2, and cost analysis of hybrid and battery electric motorcycle - Yuwono, Taufik; Sukra, Kurnia Fajar Adhi; Soewono, Respatya Teguh; Indriatmono, Dedy; Fuad, Nur Muhamad; Ma'ruf, Muhammad; Samanhudi, Ramadhani Deniartio; Kurniawan, Ade; Nugroho, Rudi Cahyo; Wahidin, Agus; Hayoto, Vebriyanti; Suryantoro, Muchammad Taufiq; Mokhtar, Mokhtar; Hidayat, Muhammad Novel; Wahono, Bambang; Pratama, Mulia; Nur, Arifin; Dimyani, Ahmad; Suherman, Suherman; Wardana, Muhammad Khristamto Aditya; Praptijanto, Achmad; Putrasari, Yanuandri; Prawara, Budi; Budianto, Hari (National Research and Innovation Agency, 2024)
The electrification of the two-wheel vehicle segment is an important strategy for decarbonising the transportation sector. This study aimed to assess the hybridisation of gasoline motorcycles with battery electric systems as an option for decarbonisation. A gasoline motorcycle that had been converted to a hybrid motorcycle was evaluated in several aspects: energy consumption, greenhouse gas (GHG) emission, and cost of energy. The vehicle was tested under the United Nations economic commission for europe (UNECE) Regulation No.40 and compared to a battery electric motorcycle. The test in internal combustion engine (ICE) mode consumed 233.31 Wh/km of specific energy, emitted 60.69 gCO2/km and cost 1.65 US-cent/km on average. The test in hybrid mode consumed specific energy at 6 % higher and 4 % lower specific energy consumption than ICE, thus not improving the carbon dioxide (CO2) emission and operating cost. In electric battery mode, energy consumption was saved by 83 %, with 35 % lower CO2 and 74 % cost savings. The battery electric motorcycle runs more efficiently with 88 % lower energy consumption, 53.8 % lower CO2 and saved cost by 82 %. If the hybrid controller is improved in future development, it could lower specific energy consumption by 41.7 %, reduce CO2 by 11.2 % and save cost by 35.7 %.